Decimal reduction times of Eschericha coli application in low temperature pasteurization of cocos nucifera endosperm beverage - Cruz, Kristelle Gay S. (2006)
ABSTRACT Pasteurization of young coconut endosperm beverage at 60°C was conducted based on the established decimal reduction time (D-value) of E. coli ATCC 25992. The coconut water beverage (CWB) medium was inoculated with the reference strain and heated to 60°C for 0, 30, 60, 90, and 120s prior to surface-plating onto Eosine Methylene Blue Agar. The calculated D-value for E. coli ATCC 25922 in CWB medium was 0.56 min ± 0.08. From this, a process schedule for the coconut water beverage was established using the 3D60°C (1.68min) and 5DD60°C (2.80min) heat treatments. Statistical analyses showed that the pasteurized CWB displayed a significant decrease (P<0.05) in their L*, a* and b* color coordinates as well as in TPC and YMC. No significant difference (P<0.05) was detected for overall acceptability, color, aroma, flavor, consistency, and mouth feel between the pasteurized and unpasteurized CWB samples. The thermal treatments proved to be adequate in the elimination of coliform in the pasteurized coconut water bever